Islamic Corporate Social Responsibility Disclosure, Profitability, and Visibility of Sharia Commercials Bank in Indonesia - Akmal, Denara (IAIN Kudus, 2024)
The purpose of this study is to analyze the effect of profitability and visibility on Islamic Corporate Social Responsibility Disclosure (ICSRD) of Islamic Commercial Banks in Indonesia for the period 2020 – 2022. This research is a quantitative study using secondary data from the Islamic Commercial Bank's Annual Reports and Sustainability Reports. The effects are examined based on content analysis of 9 Islamic Commercial Banks in Indonesia using a purposive sampling technique. The results showed that profitability and visibility simultaneously had a significant effect on the ICSRD of Islamic Commercial Banks in Indonesia for the period 2020 – 2022. However, partially the profitability did not affect ICSRD. Meanwhile, the visibility has a significant effect on ICSRD partially. The results of this study are expected to provide a reference for Islamic Commercial Banks policymakers to always improve the ICSR to maintain customer confidence in the operations of Islamic Commercial Banks in Indonesia.